Dynamics of Social Change and Perceptions of Threat - Frie, Ewald; Kohl, Thomas; Meier, Mischa (2024)
Why do things change at certain times and not at others? The contributions collected in this volume approach this question from the perspective of threat. Defined as the self-alerting which goes on within societies and social groups, threats open up windows of opportunity for change - though not always the ones hoped for by those who raised the alarm in the first place. But once threatened, social orders previously taken for granted become visible, debateable and therefore changeable. Looking at the relationship between threat and social change with thematic, spatial and temporal foci, the contributions of this five-section volume treat topics ranging from systems of belief in Ancient Europe to droughts in twentieth century Australia, from medieval urban riots to organized crime and peaceful protest nowadays.